Dynamics of soliton and mixed lump-soliton waves to a generalized Bogoyavlensky-Konopelchenko equation - Ismael, Hajar F.; Ma, Wen-Xiu; Bulut, Hasan (Iop Publishing Ltd, 2021)
We study dynamics of soliton waves, lump solutions and interaction solutions to a (2+1)-dimensional generalized Bogoyavlensky-Konopelchenko equation, which possesses a Hirota bilinear form. Multi-soliton solutions, one-M-lump solutions, and physical interactions between solitons and 1-M-lump solutions are presented. By using a positive quadratic function, lump solutions and their interaction solutions with kink and solitary waves are also generated. To show dynamical properties and physical behaviors of the resulting solutions, 3D-plots and contour plots at different times are made and analyzed.
Keywords: hirota bilinear from; n-soliton solution; m-lump solution; quadratic solution; interaction solution